The Shift of Techno-Economic Paradigm and Its Effects on Regional Disparities - Vesa Harmaakorpi; Arto Haikonen; Ilkka Kauranen (European Regional Science Association (ERSA), 2003)
During the 1900's we first lived thorough shift from the agricultural era to the industrial era. Nowadays, we are in the middle of the shift from the industrial era to the information era. The new era has several definitions based on different theories. At the same time, we talk about information society (knowledge is forming the main productivity factor), network society (new communication technology is connecting people), post-industrial society (change in production paradigm), service society (emphasis on services instead of production), expert society (increasing importance of skilled people and experts), learning society (learning ability becomes a critical factor), postmodern society (modernisation leads to individualism), innovation society (innovation is the driving force of economic growth), risk society (risks and uncertainty are increasing in society) and consumer society (consumer needs steer economic activities) These definitions reflect the different points of view of assessing the development we have been experiencing during the recent years. Each of these definitions emphasises different phenomena embedded in the change of present techno-economic paradigm, and each of them builds a basis for the assessment of the requirements of the changing environment. Although the definitions and theories describing the present change are mostly very abstract, some concrete indicators can be determined to describe the phase of the trajectory in the changing process of the society. The changes in the society should be assessed at regional level, especially as regional dimension is gaining importance in the development policies at the European level. In the regional context the question to rise first is, how the shift of techno-economic paradigm appears in the regional level and what its effect is on emerging regional disparities. Secondly, is it possible to evaluate, how the region's adaptability to the shift of techno-economic paradigm correlates to its economical success. In the current study, an indicator is created to describe a regions' adaptability to the shift of techno-economic paradigm. The variables included in the adaptability indicator are derived from the theories describing the present society. The Finnish urban regions are used as the source of empirical data in this study. All Finnish urban regions are assessed based on the adaptability indicator and further on, the values of the adaptability indicator are compared to the respective values of indicators describing the economic success of the same regions.. Admittedly, the adaptability indicator does not describe the studied phenomenon completely, it might even be considered provocative. However, it gives some interesting results about the different kinds of development trajectories of urban regions, and gives valuable information for regional decision-making.
Keywords: 330